2014
DOI: 10.3390/s140406877
|View full text |Cite
|
Sign up to set email alerts
|

Enhance the Pyroelectricity of Polyvinylidene Fluoride by Graphene-Oxide Doping

Abstract: The high quality properties and benefits of graphene-oxide have generated an active area of research where many investigations have shown potential applications in various technological fields. This paper proposes a methodology for enhancing the pyro-electricity of PVDF by graphene-oxide doping. The PVDF film with graphene-oxide is prepared by the sol-gel method. Firstly, PVDF and graphene-oxide powders are dispersed into dimethylformamide as solvent to form a sol solution. Secondly, the sol solution is deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…To further improve the piezoelectric output various nanofillers such as clay , carbon nanotube , graphene , ZnO , BaTiO 3 , and PZT have been added to PVDF. These nanofillers either enhance the piezoelectric output or improve the β‐phase content of PVDF.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the piezoelectric output various nanofillers such as clay , carbon nanotube , graphene , ZnO , BaTiO 3 , and PZT have been added to PVDF. These nanofillers either enhance the piezoelectric output or improve the β‐phase content of PVDF.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [14] obtained similar results for nylon-6/poly(vinylidene fluoride) (PVDF) blends. Moreover, graphene oxide has also revealed a good nucleating ability towards several semi-crystalline polymers, including for instance isotactic polypropylene (iPP) [29][30][31], PVDF [32][33][34], PCL [35], and the two polymers object of the present study, PLLA and PBS [36,37]. As such, in the current work the dual role of GO added in low amounts to PLLA/PBS blend is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have shown that mechanical and thermal properties of PVDF are improved by the addition of G [19,29,37,38]. …”
Section: Methodsmentioning
confidence: 99%